Das raumordnerische Konzept der Städteverbünde und seine Umsetzung in der landesplanerischen Praxis - Greiving, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
The paper focuses on city alliances, designated recently by federal state’s regional planning in order to create combined central-places. The effectiveness of this concept has been reduced in the past due to the missing binding designation of shared functions. Contractual agreements have been identified here as an appropriate instrument in the last years. The planning practise of these alliances triggered by new, more concrete objectives laid down by regional planning will be evaluated by examples from Saxony, Thuringia and Bavaria.